PEMBENTUKAN KARAKTER SOPAN SANTUN ANAK USIA 12-15 TAHUN DI RW 03 DESA BEDUG KECAMATAN PANGKAH KABUPATEN TEGAL (Unnes Civic Education Journal, 2022)
Courtesy is a basic character that everyone should have to interact and socialize well in society. But in reality, this character is getting neglected, especially among children aged 12-15 years in RW 03 Bedug Villege. The purpose of this study was to determine the character formation of children aged 12-15 years in RW 03 Bedug Village, Pangkah District, Tegal Regency along with the driving and inhibiting factors. This study uses a qualitative method using observation, interviews, and documentation techniques to obtain data. The validity of the data was tested by using triangulation of sources and methods, while data analysis was carried out starting from data collection, data reduction, data presentation, and concluding. The results showed that the formation of the polite character of children aged 12-15 years in RW 03 Bedug Village, Pangkah District, Tegal Regency was carried out by the family and community, based on the prevailing politeness values by providing understanding and applying habituation, as well as exemplary. to shape the child's personality into a person of polite character so that later it can be well received in society. The driving factors for the formation of the polite character of children aged 12-15 years include instincts/instincts in children, desires, and wills, as well as support from family and society. While the inhibiting factors for the formation of polite character for children aged 12-15 years are the children's customs/habits in behaving and behaving, as well as the attitudes and behavior of peers.